2015
DOI: 10.1182/blood.v126.23.322.322
|View full text |Cite
|
Sign up to set email alerts
|

Midostaurin in Combination with Intensive Induction and As Single Agent Maintenance Therapy after Consolidation Therapy with Allogeneic Hematopoietic Stem Cell Transplantation or High-Dose Cytarabine (NCT01477606)

Abstract: Background: Internal tandem duplications (ITD) in the receptor tyrosine kinase FLT3 occur in roughly 25% of younger adult patients (pts) with acute myeloid leukemia (AML), implicating FLT3 as a potential target for kinase inhibitor therapy. The multi-targeted kinase inhibitor midostaurin shows potent activity against FLT3 as a single agent but also in combination with intensive chemotherapy. Aims: To evaluate the feasibility and efficacy of midostaurin in combination with intensive induction the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Only 4 grade 3/4 AEs were suspected to be related to midostaurin. These preliminary data suggest that post-transplantation midostaurin may be effective in patients with FLT3-ITDepositive AML, particularly those with a high FLT3-ITD:WT ratio [70].…”
Section: Published Data On Flt3 Tkis Given After Transplantationmentioning
confidence: 79%
“…Only 4 grade 3/4 AEs were suspected to be related to midostaurin. These preliminary data suggest that post-transplantation midostaurin may be effective in patients with FLT3-ITDepositive AML, particularly those with a high FLT3-ITD:WT ratio [70].…”
Section: Published Data On Flt3 Tkis Given After Transplantationmentioning
confidence: 79%
“…For example, this technology would be useful to determine the prognostic and therapeutic impact of the recently identified, rare N767 mutation that confers resistance to certain FLT3 inhibitors in vitro [12,56]. A potential disadvantage is that gene panel testing can have longer turnaround times (3-20 d) [46] than conventional PCR-based methods (48-72 h) currently used to screen patients in clinical trials [16,57,58].…”
Section: % 3 Dmentioning
confidence: 99%
“…Midostaurin maintenance was investigated in a phase 2 trial that included 40 patients with newly diagnosed FLT3‐ITD AML post HCT. The trial showed a low incidence of relapse in patients with both high and low FLT3‐ITD mutant to wild type ratio (5% and 12%, respectively) . A randomized, open‐label, phase 2 exploratory trial (RADIUS) compared midostaurin in combination with standard of care vs standard of care in newly diagnosed patients (n = 60) with FLT3‐ITD AML who were in first CR after HCT .…”
Section: Post‐remission Treatment Approachesmentioning
confidence: 99%